El Apocalipsis de Juan: Aspectos generales en cuanto a su simbología (Theological Kronos, 2018)
The Revelation to John is a book rich in symbols. The allusion to characters that resemble something out of horror stories or science fiction, the mention of terrible cosmic events that affect humanity, the heavenly and earthly battles that end in destruction and death are some of the recurring themes that the author uses in order to communicate his message. However, despite the obvious interpretative complications that this may cause, the author expresses himself in that way in order to be clear, vivid, profound and near to the reality that his community is living in.
Keywords: clarity, interpretation, reveal, updating.